Early Carthusian Script and Silence - Gilbert, Bennett (Cistercian studies quarterly, 2014)
The article discusses the early Carthusian concept of communication. Information includes a review of historical background of the concept, related documentary texts, and the two-step structure of its development. It highlights the views of Carthusians Bruno, Guigo I, and Guigo II concerning the role of the Carthusian scribal work in spiritual development.